Model of Psychological care for women victims of domestic violence sheltered in temporary shelter homes. HRT. - Deza Villanueva, Sabina Lila (2016)
Homes in temporary shelter should contribute to the emotional recovery of victims of violence and a change or modification of behavior based on the establishment of healthy relationships, promoting their autonomy and recognition of their abilities. The psychological recovery of women victims of violence is critical to feeling person and woman, with rights and values that must be protected, only then can start a dignified, independent and free life. At the same time, recovery is invaluable for improving quality healthy family context. Emerging shelter homes, Basic Principles on the psychological intervention for women housed in HRT, considerations related to the emotional state of women victims of domestic violence and Good professional practices: Considering these aspects in this article discusses the following topics are developed. Finally, the proposed model describes psychological care from both the individual level intervention that includes crisis intervention and counseling; also considering the group level from a psychoeducational approach.